Performance analysis of 30 MeV electron linac with a new injector system - Gokov, S.P.; Makhnenko, L.A.; Khodak, I.V.; Shopen, O.A. (Вопросы атомной науки и техники, 2009)
The present paper deals with the problems of 30 MeV electron linear accelerator (LINAC-30) upgrading to attain optimum beam spectral characteristics. As one of the LINAC-30 upgrading variants, consideration has been given to a possible use of the injection system for LINAC-30, which is in general similar to the 60 MeV electron linear accelerator (LINAC-60) injector and which includes a low-voltage 25keV electron source and a five-cavity standingwave buncher. Two possible configurations of the upgraded accelerator have been considered. Schematically, they can be represented as follows: 1) a new injector and a long section (4.41 m) of the basic accelerating channel; 2) a new injector, a short (0.83 m) section (section N 1) currently operating at a retarded phase velocity of the wave, and a long section (section N 2). Numerical modelling of particle dynamics in the accelerating channel has been performed for the two cases. Based on the results obtained, assumptions are made as to the most optimum configuration of the upgraded accelerator.